SIMULASI PENGUKURAN KAPASITAS BEBAN SAMPAH PADA OTOMATISASI PENGAMBILAN SAMPAH DI SUNGAI - Reka Rusydina; Yohannes Dewanto (JURNAL TEKNOLOGI INDUSTRI, 2020)
Automatic garbage collection is an effort to overcome the problem of garbage accumulation in the river. Increasing the automation system of the load on waste can maximize the performance of waste management in watersheds such as rivers. This is the basic thought of the author in making a simulation tool to indicate the burden on the automation of waste collection in the river. In this simulation tool has an automatic marker to notify the amount of load received when passing through river water, these settings can determine the LEDs that  turn on automatically. The process of taking garbage in a river is based on the weight of the load on the garbage to be taken to the shelter. The design of this tool consists of two stages, namely the design phase of hardware and software. The hardware used in the design of this tool is the power supply as a voltage and electric current to the components used, the load cell for the weight sensor is able to convert the measured weight into the form of electrical signals, the arduino uno 328P microcontroller as the controller, while the software on This tool uses the LCD to display data and LEDs as an indicator that the load on the load cell sensor has exceeded the specified limit. This study uses a Load cell sensor to measure the load being weighed. Sensor output in the form of voltage in the order of millivolts. The load that is being measured will be displayed on the LCD and the setting of the waste load that goes to the shelter. Final testing of the entire system shows that the tool is able to process the weighting load more quickly. Tests on the entire system also show that when the tool weighs a load of rubbish with a weight of 1500gram and 2000gram. Keywords: load garbage, load cell, microcontroller, LCD and LED